2007
DOI: 10.1203/pdr.0b013e3180536609
|View full text |Cite
|
Sign up to set email alerts
|

GJB2 and GJB6 Mutations in Children with Congenital Cytomegalovirus Infection

Abstract: Congenital cytomegalovirus (CMV) infection is a leading cause of sensorineural hearing loss (SNHL) in children. Whether connexin mutations are factors in the development of CMV-related hearing loss has not been explored. We examined gap junction protein beta-2 (GJB2) and gap junction protein beta-6 (GJB6) mutations in 149 children with congenital CMV infection and 380 uninfected neonates. Mutations in GJB2 and GJB6 were assessed by nucleotide sequencing and polymerase chain reaction (PCR) methods, respectively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
24
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 31 publications
0
24
0
Order By: Relevance
“…The pathogenesis of SNHL in children with congenital CMV infection remains not well understood. Ross et al initially found that the mutation rate of GJB2 in children with CMV infection and hearing loss was higher than those in children with CMV infection and normal hearing (20).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The pathogenesis of SNHL in children with congenital CMV infection remains not well understood. Ross et al initially found that the mutation rate of GJB2 in children with CMV infection and hearing loss was higher than those in children with CMV infection and normal hearing (20).…”
Section: Discussionmentioning
confidence: 99%
“…Ogawa et al (19) reported that congenital CMV infection and GJB2 mutations were identified in 15 and 24%, respectively, of 67 children with severe SNHL. Ross et al (20) found that the overall frequency of GJB2 mutations in children with CMV infection and hearing loss was higher than that in children with CMV infection and normal hearing (21 vs. 3%).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…38 Thus, the presence of a single recessive allele in an individual with hearing loss may not simply represent a carrier state and should be interpreted cautiously when providing genetic counseling. Other factors, such as infection, may be co-occurring with mutations in Cx26/30 39 warranting further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The present prospective study evaluated the effect of cochlear implantation in deaf children with asymptomatic CMV infection. Congenital CMV infection was confirmed by CMV DNA testing of neonatal urine; however, a direct causal relationship between the CMV infection and the hearing loss was not proven because genetic testing to identify mutations, such as in the GJB-2 gene, was not performed [17]. However, the clinical course of the patients’ audiologic findings strongly suggests a positive correlation between CMV infection and deafness in these cases.…”
Section: Discussionmentioning
confidence: 99%